The safety-hygiene air corridor between UK and Spain will coexist with COVID-19 - Lázaro Florido-Benítez (Logistics, 2022)
Background: The main goal of this case study is to analyze the air traffic, air cargo, and the safety-hygiene air corridor between UK and Spain, in airports managed by MAG Group (UK) and AENA Group (Spain). Methods: To review the specific paradigm of research which discusses, investigates, and analyses the air traffic, air cargo, and the safety-hygiene air corridor between UK and Spain at airports managed by MAG (UK) and AENA (Spain). Results: The air traffic that airlines project onto the UK-Spain corridor has decreased due to the pandemic, but the result of this research shows that in the medium term, to implement the new Safety-Hygiene Air Corridor (SHAC) will return to economically nurture airlines, airports and destination thanks to vaccines, the digital COVID-19 certificate that will give more confidence to passengers to travel, and with new COVID-19 safety regulations at airports and airlines. Furthermore, the results of the research show the need to create Safety-Hygiene Air Corridor Elements (SHACE) to improve the air activity of these countries. Conclusions: The study contributes towards providing solutions such as those we propose in this study, the UK-Spain SHAC and SHACE will guarantee the value of corridors between countries, reduce the uncertainty of airlines, organizations, and passengers, to restore the tourism and aviation industries.
Keywords: 650; air cargo; air corridor; airlines; airports; digital COVID certificate; tourism; travel insurance